Effectiveness of Video-Assisted Task-Based Learning to Improve Students’ English Speaking and Listening Skills - Dewi Sartipa (Austronesian: Journal of Language Science & Literature, 2026)
This study examines the effectiveness of video-assisted Task-Based Learning (TBL) in enhancing students’ English speaking and listening skills, particularly in the context of job interviews. Employing a pre-test and post-test experimental design, the research involved two groups of 20 students from the English Study Program at the University of Muhammadiyah Kotabumi. The experimental group utilized videos as part of TBL, while the control group engaged in conventional learning methods. The independent t-test was used to analyze differences in skill improvement between the two groups. The results indicated that the experimental group, using video-based TBL, demonstrated significantly higher improvements in both speaking and listening skills. Post-test scores revealed an average of 78.7 in speaking and 80.3 in listening for the experimental group, compared to 68.4 and 70.9 for the control group, respectively. Statistical analysis revealed significant differences with p-values of 0.0001 for speaking and 0.0003 for listening, respectively. These findings suggest that video-assisted TBL is an effective method for improving English skills, particularly for professional contexts like job interviews. The study highlights the potential of incorporating multimodal resources like video into language learning, offering students a more authentic and engaging learning experience. The implications for teaching practices emphasize the need for integrating technology to enhance language learning and better prepare students for real-world communication challenges.